Amsal 1:7 sebagai Fondasi Pendidikan Spiritual Kristen: Rekonstruksi Pedagogis bagi Pembentukan Karakter dan Kematangan Spiritual - Eston Warani (Jurnal Salvation, 2026)
This study aims to implement the values of Proverbs 1:7 in Christian spiritual education to foster character formation and spiritual maturity. In the era of information disruption, spiritual education faces the challenge of secularism, which separates intellectual intelligence from moral foundations. Using a qualitative-descriptive method with a literature study approach, the findings reveal that the “fear of the Lord” is not merely a sense of fear, but an ontological orientation that produces character integrity, emotional-spiritual maturity, and ethical commitment. The study concludes that Proverbs 1:7 plays a significant role in shaping students’ character integrity and spiritual maturity. The concept of the “fear of the Lord” cannot be reduced to a mere emotional response of fear, but must be understood as an existential disposition that directs the whole of human life toward God. Proverbs 1:7 holds a crucial role in Christian spiritual education. The value of the “fear of the Lord” serves as a foundation for forming character, humility, and spiritual habits among learners. True knowledge is rooted in a relationship with God. Practically, this implies that Christian spiritual education should not be limited to the transmission of knowledge, but must also emphasize life transformation that results in mature and integrative character formation. Abstrak: Penelitian ini bertujuan mengimplementasikan nilai-nilai Amsal 1:7 dalam pendidikan spiritual Kristen untuk membangun karakter dan kematangan spiritual. Di era disrupsi informasi, pendidikan spiritual menghadapi tantangan sekularisme yang memisahkan kecerdasan intelektual dari fondasi moral. Menggunakan metode kualitatif-deskriptif dengan pendekatan studi pustaka, hasil penelitian menunjukkan bahwa "takut akan Tuhan" bukan sekadar rasa gentar, melainkan orientasi ontologis yang menghasilkan integritas karakter, kematangan emosional-spiritual, dan komitmen etis. Kesimpulan penelitian adalah bahwa Amsal 1:7 berperan signifikan dalam membentuk integritas karakter dan kedewasaan spiritual peserta didik. Konsep “takut akan Tuhan” tidak dapat direduksi menjadi emosi ketakutan semata, tetapi harus dipahami sebagai disposisi eksistensial yang mengarahkan seluruh kehidupan manusia kepada Allah. Amsal 1:7 memiliki peran penting dalam pendidikan spiritual Kristen. Nilai “takut akan Tuhan” menjadi dasar dalam membentuk karakter, kerendahan hati, dan kebiasaan spiritual peserta didik. Pengetahuan sejati berakar pada relasi dengan Allah. Secara praktis, Dengan demikian, pendidikan spiritual Kristen tidak hanya berorientasi pada pengetahuan, tetapi juga pada transformasi kehidupan yang menghasilkan karakter yang matang dan berintegritas